Efficiency optimization of an induction machine using optimal flux control - Sidek, N. K. (IEEE, 2014)
This paper presents the efficiency optimization of a variable speed induction machine (VSIM) using an Optimal Flux Control (OFC). To optimize the efficiency, an approach called as Maximum Torque per Ampere (MTA) algorithm was used to provide the constant optimal flux (COF) during the speed control, where the minimisation of the winding losses is considered along the operation. In this paper, the total power and total power loss during machine motoring is presented. The performance of the proposed OFC design is compared with the conventional open-loop scalar-control (OLSC) method. From the finding, it was found that the COF approach provides better performance than the OLSC in terms of settling time, steady-state error and efficiency.